PENGARUH PEMBERIAN STOSA PADA PERTAMBAHAN PANJANG BADAN, TINGGI BADAN DAN LINGKAR DADA KAMBING KACANG - , CHRISTIDA ESTU WASTIKA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Goat require nutrients for maintenace, growth, reproduction, pregnancy, and production of meat, milk, and hair. Growth is influence by the quality and quantitiy of food given. Research of STOSA as supplement aims to determine the effect of STOSA on body length, wither height and heart girth kacang goat. Research was conducted using 12 goats that divided into 4 groups. Group B, C and D respectively treated with 2 ml, 4 ml and 8 ml STOSA and water as solvent added until the volume of 8 ml, and group A as control were given 8 ml of water twice a day for 5 weeks. Body length, wither heigh, and heart girth measurements were done at the first and fifth week. The data analyzed by one way anova and Shapiro-Wilk. The result showed that at the fifth week added STOSA, the average body length of group A, B, C, and D respectively was 46,33±2,52, 49,5±2,18, 46,5±0,87, and 49,5±1,5 cm. Average of wither height 53,17±4,31, 52,83±1,04, 52±2,18, and 53,5±0,87 cm. The average of heart girth 50,63±0,29, 51±3,12, 51,23±2,25, and 55,33±5,5 cm. The analysis described that STOSA was not affect the body length, wither height, and heart girth kacang goat (P>0,05).